A unique tripartite collision tumor of the esophagus: A case report. Issue 49 (December 2017) - Schizas, Dimitrios; Michalinos, Adamantios; Alexandrou, Paraskevi; Moris, Demetrios; Baliou, Evangelia; Tsilimigras, Diamantis; Throupis, Theodore; Liakakos, Theodore
Abstract: Rationale: We report a unique case of a tripartite esophageal collision tumor consisting of three separate histologic types. Patients concerns: Therapeutic dilemmas on the proper treatment of those rare neoplasms remain unanswered considering both proper surgical therapy and adjuvant therapy. Diagnose: In this paper, we report a unique case of a patient with a tripartite esophageal collision tumor consisting of a small cell carcinoma, an adenocarcinoma of medium differentiation and a signet ring cell carcinoma. Diagnosis is difficult as clinical presentation of the patient was undistinguishable from other, commoner tumor types. Interventions: The patient's diagnostic and therapeutic course along with available data on the collisions tumor's biological behavior and treatment are briefly discussed. Outcomes: Esophagectomy is the best treatment options for these patients. Unique nature of this tumor demands aggresive oncologic treatment. Lessons: Collision tumors are rare neoplasms consisting of distinct cell populations developing in juxtaposition to one another without any areas of intermingling. Various cell types can be found. However, collision neoplasms of the esophagus combining adenomatous and neuroendocrine components are exceedingly rare, with only 5 cases described to date in the literature. Given their rarity, limited information is available on their tumorigenesis, biological behavior and clinical course. In general, these tumors are aggressive neoplasms and significantly affect patient treatment and prognosis.